PEMBUATAN BIOETANOL DARI EMPULUR DAN LIMBAH SERAT SAGU DENGAN METODE KIMIAWI DAN ENZIMATIS - Ina Winarni; Totok K. Waluyo; Sri Komarayati (BRIN Publishing, 2019)
Sago (Metroxylon spp.) is one of the native Indonesian plants that can be converted into biofuel or bioethanol. All parts of sago: starch, stem and midrib could be converted into bioethanol. The objective of this research is to determine ethanol production techniques made of pith and sago waste fiber using chemical and enzymatic methods. Bioethanol technique used was chemical based using hydrochloric acid solution (HCl) of 3.1; 6.2; 9.3 and 12.4% with substrate concentration of 15% (dw) and then heated by autoclave at 121–127 °C for 5, 10 and 15 minutes; pressure of 1–1.5 bar. The enzymatic method was undertaken using 0.15 ml alpha amylase enzyme and 2%, 3% and 4% cellulase. Fermentation was conducted using 0.21 g of urea addition, 0.12 g of NPK and 0.48 g of yeast for 4 days. Results showed that the pith yielded higher reducing sugar content and ethanol content than sago fiber waste either by chemical method (446.34 g/l, 51.65%) or enzymatic (15.39 g/l, 16.82%). Greater of cellulase concentration from 2% to 4% could not improve the yield of ethanol either made from pith or the wasted sago fiber through hydrolysis process.